A comparative study on consumer perception towards Branded products and unbranded products in offline and online business (International Journal of Food and Nutritional Sciences, 2022)
The study investigates how consumers perceive branded and unbranded products in both physical and online stores. The study collected primary data from 200 participants from Chandrapur districts through a field survey method. The investigation underscores the importance of branding in consumer buying choices and the changing consumer conduct in the retail sector. It indicates that consumers typically see branded items as symbolizing superior quality, reliability, and status, whereas unbranded products are seen as more budget-friendly and value-oriented. The study find that consumers prefer to buy branded products from offline mode and majority of the respondents are emotionally attached with the branded products and it create a positive impact on the consumer awareness.